Riqueza de pobre: um estudo em antropologia da saúde - Costa, Ana Maria (1978)
This dissertation has a central theme the representations of human body, work and health/illness. It is,in fact,a study on ideology in which we have used the technic of discourse analysis. This study has been elaborated with a basis on six month of field research, with hand workers, rural migrants, living in Vila Buritis, Planaltina, Distrito Federal. The resulting text is divided into three parts. In the first part we have gathered the usual information for the presentation of a dessertaticn. Thus,it contains the outlining of the theme to be treated and the researched universe (the kind of informers and local of research), as well as the information about the conditions of realization of a field work, of anthropological nuture, with urban workors.In the second part, we have presented an analysis of the categcries of body and work percepticn and the category of the most frcqucnt illness in the porülàir nosolòçry. 'The third part contains the analysis of the data about the consumption of med'5 caments, stressing its compatibility with the forms of body í . . perception and the subjection to, physical exhaustion to , which thehand worker is exposed,.- considering that his levei of life does not allow a replacement of the energy lost at work. The presented analysis has had as a general theorical presupposition the idea that. the set of representations which man olaborates about hímself,h’>s relation with other man and with nature depends on the modo in which he produces his life. Thus, the representations, far froirt being disconnected reveries about the nature of the world and the society are a way of thinking necessarily determined by the objective conditions of existence and therefore they are a way to reach a comprehension of man. But it won't obviously be an abstract man, since the objective forms of determination of consciouness vary not only historically but also synchroncusly, in a same society. Among these general questions about the tenor of the representations, the choice of the study of a specific way of bccT conceptíon, of a particular category, may be seen as an attempt tc comprehend the actualization of the presupposition of the consciouness. That is, how a certain category of persons.whose work is based exclusively on physical strcngth, think about themselves which is the concoption of body and its two antithetic aspects, health and illness, for those who possess only the own body as a work instrument and therefore as a survival instrument. The work, as the only way individuais have to earn their living, is a privileged analysis field, as well as thinking of body health and illness is a privileged field for the studied category. Thus, whenever it was asked to define its concepts of health, the studied group was not able to do it without a reference to its work. Therefore, the conceptions of health and illness stresses an intimai relation with the kind of instrumental utilization of the body to which one category of worker, the hand worker , is exposed. For those whose work expose them to a permanent wearing out, aid if the conditions and the level of life allow a replacement of energy lost at work, some strategies of body care are created. In this specific case, since accessibility to food - the principal resource of maintenance and replacement of energy is more and more limited, the consumption of medicaments (freely and popularly distibuted) becomes of a great importance to these individuais and their families.